Biocrude from biomass: Pyrolysis of rice straw - Razi, Ahmad; Khairuddin, Md lsa; Khairul Nizar, Ismail; Khudzir, Ismail (Forest Research Institute Malaysia (FRIM), 2011)
Seminar on Biomass for Biofuels and Value-Added Products 2009 organized by Forest Research Institute Malaysia (FRIM) & Universiti Malaysia Pahang from 27th - 28th October 2009 at The Saujana, Kuala Lumpur, Malaysia.